Fat and protein content in Turkish hazelnut (Corylus colurna L.) in Kastamonu province - Ayan, Sezgin; Ünalan, Erkan; İslam, Ali; Sakıcı, Oytun Emre; Yer, Esra Nurten (Artvin Coruh Universitesi Orman Fakultesi Dergisi, 2018)
Turkish hazelnut (Corylus colurna L.), the mother land and natural spreading area of which is Anatolia, is one of the important hazelnut species in Turkey. Moreover, thanks to its adaptation capability to extreme climate and poor soils conditions, it is a forest tree species playing a key role in climate change scenarios. Turkish hazelnut, a Euro-Siberian flora element in Turkey, is a taxon present in the ''Low Risk'' category according to the IUCN Red List. Turkish hazelnut which spreads disorderly-partially and in an isolated way in small stands, groups, clusters as individuals, has the most intense spreading in the Northwestern Anatolian forests in Anatolia. The fruits of the Turkish hazelnuts are being utilized as a valuable traditional medicinal herbal product in different regions of the world. This paper aims to identify and to compare the fat and protein composition of Turkish hazelnut kernels among and within four populations (Ağlı-Tunuslar, Ağlı-Müsellimler, Araç-Güzlük and Tosya-Küçüksekiler) in Kastamonu region. According to the results of the study; the mean values of fat and protein content were found to be 62.78% and 16.32% respectively. In terms of protein values, significant differences were identified among the populations. However, there were no significant differences among the populations regarding the fat values. The highest median value of the protein was found in Ağlı-Tunuslar with a rate of 18.43%. There is no variation within populations as to fat and protein values. The study suggests that similar studies be continued in detail based on different ecological conditions and genotypes.
Keywords: Türk fındığı; Meyve; Yağ; Protein; Popülasyon çeşitliliği; Turkish hazelnut; Kernel; Fat; Protein; Population diversity; 2. Zero hunger; 13. Climate action; 15. Life on land; 3. Good health